A cost‐consequence analysis of early detection of AD in the MOPEAD project — A project within the EU research agenda IMI‐2: Other innovative programs and practices. (7th December 2020) - Wimo, Anders; Belger, Mark; Bon, Jaka; Vugt, Marjolein; Jessen, Frank; Kramberger, Milica G; Jamilis, Laura; Johansson, Gunilla; Rodrigo, Adrián; Rodriguez‐Gomez, Octavio; Sannemann, Lena; Stoekenbroek, Malou; et al.
Abstract: Background: "Models of Patient Engagement for Alzheimer's Disease" (MOPEAD), is a project within the EU‐Innovative Medicines Initiative (IMI‐2) research agenda, aiming at improving early detection of Alzheimer´s disease (AD). Methods: Four screening strategies ("runs") were tested in five countries (Germany, the Netherlands, Slovenia, Spain and Sweden): Run 1 used a web approach, Run 2 held open houses at memory clinics, Runs 3 and 4 took place at clinics (primary care and type2‐diabetes specialist settings respectively). Persons at risk of AD were offered referral to a memory clinic (WP3). The primary health economic outcome was the cost per true positive case (TP) of mild cognitive impairment (MCI) or AD from the screened population. Also costs per screened case, cost per case entering the memory clinic and the number needed to screen (NNS) to identify a TP case were analysed. A comprehensive sensitivity analysis was accomplished. Results: Of 2847 screened persons, 1117 screened positive, 398 were evaluated at WP3 and of those, 236 were diagnosed with AD or MCI. The cost per TP of those screened was 1, 190€ in Run 4, 1, 530€ in Run 3, 2, 722€ in Run 2 and 3, 115€ in Run 1. The results in the sensitivity analysis that was regarded as best to reflect real world were 1, 443€/TP in Run 4, 1, 856€ in Run 3, 2, 714€ in Run 2 and 3, 098€ in Run 1. The NNS was 6 in Run 4, 8 in Runs 2 and 3 and 30 in Run 1. The cost per screened was 103€ in Run 1, 338€ in Run 2, 204€ in Run 3 and 212€ in Run 4. There were great country differences. Conclusion: Although Runs 3 and 4 had lower costs per TP/screened population than Runs 1 and 2, the capacity of Runs 3 and 4 to identify cases with AD‐risk must be discussed. Thus, new diagnostic strategies (Runs 1 and 2) may be valuable after modifications. For example, one challenge in Run 1 was to get in touch with people who screened positive, and in Run 2, the cost‐effectiveness may improve by integrating Run 2‐screening and memory clinics (diagnose confirmation).